Regulation of Location-Specific Externalities - Eirik S. Amundsen; Lars Gårn Hansen; Hans Jørgen Whitta-Jacobsen (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we study regulation of externalities involving many small-scale polluters, where the damages from emissions depend on the polluters' locations. Examples include nutrient and pesticide emissions from farms, particulate emissions from vehicles and home heating units, emissions of hazardous chemical compounds from small business etc. With such emission problems, regulatory authorities often apply a combination of firm-level, possibly differentiated standards for `cleaner' technologies, and market-level, undifferentiated dirty input regulations. We establish general principles for how such regulations should be designed and combined. We find that the optimal regulation design crucially depends on the type of cleaner technologies available to polluters. If these are `emission capturing', optimal technology standards encourage the use of cleaner technologies in both high and low damage areas, while if they are `input displacing', optimal technology regulation encourages cleaner technologies in high damage areas, but discourages their use in low damage areas. Regulation should always discourage the use of dirty input and the optimal regulation intensity may be substantial, particularly if the available cleaner technologies are input displacing.
Keywords: H23; Q58; D62; 330